SGLT-2 Inhibitors—a Culprit of Diabetic Ketoacidosis Postbariatric Surgery - Qasim Zafar Iqbal; Danil Mishiyev; Muhammad Raphay Niazi; Zeeshan Zia; Saud Bin Abdul Sattar; Abdullah Jahanghir; Shahed Quyyumi (Case Reports in Critical Care)
Sodium-glucose cotransporter-2 SGLT2 inhibitors are antihyperglycemic drugs that are currently being recommended as second-line therapy for patients with diabetes mellitus. They have grown increasingly popular over recent years, as they have been shown to have some protective effects on the heart and kidneys, both organ systems that diabetes mellitus has shown to have deleterious effect on over time. Despite their growing popularity, they have been found to increase the risk of euglycemic diabetic ketoacidosis (DKA). There is an increasing body of literature detailing cases of euglycemic DKA after bariatric surgery. We present a case series of three cases of euglycemic DKA postbariatric surgery in patients with an underlying history of type 2 diabetes mellitus, who were being treated with SGLT2 inhibitors prior to the surgery. All three patients reported to the emergency room with signs, symptoms, and clinical findings of euglycemic DKA. The AACE recommends SGLT2 inhibitors to be discontinued at least 24 hours prior to surgery and resumed when a patient resumes a normal diet. Our patients presented with euglycemic DKA after bariatric surgery, and we recommend more research should be done targeted at the prolonged postoperative course of patients on SGLT-2 inhibitors and into creating specific guidelines for their use after bariatric surgery.